The Role of Heart Rate, Body Temperature, and Respiratory Rate in Predicting Anastomotic Leakage following Surgery for Rectal Cancer - Jiajun Luo; Hongxue Wu; Yue Jiang; Yu Yang; Jingwen Yuan; Qiang Tong (Mediators of Inflammation)
Objective. To explore the value of the heart rate, body temperature, and respiratory rate in the early prediction of anastomotic leakage after rectal cancer surgery. Methods. Clinical data from patients with rectal cancer who underwent anterior rectal resection in the Department of Gastroenterology, Renmin Hospital of Wuhan University, from January 2017 to December 2019 were collected and analyzed retrospectively. Based on the occurrence of anastomotic leakage after surgery, the patients were divided into two groups: those with and without anastomotic leakage. The quantitative values of the heart rate, body temperature, and respiration rate at day 7 postsurgery were compared between the two groups. The ROC curve was used to analyze their role in the early prediction of anastomotic leakage. Results. Among 441 patients with rectal cancer, 30 (6.81%) had clinical anastomotic leakage and were diagnosed at 7±3 days postsurgery. Within 7 days postsurgery, the heart rate, body temperature, and respiratory rate in the anastomotic leakage group were higher than those in the nonanastomotic leakage group. The differences in heart rate (1-5 d), body temperature (2-7 d), and respiratory rate (1-7 d) were statistically significant (P<0.05). The three ROC curves were drawn, respectively. The predictive value of the heart rate is greatest at days 2-3 postsurgery. The predictive value of the body temperature is greatest at days 4-6 postsurgery. The predictive value of the respiratory rate is best at days 1-4 postsurgery. Conclusion. The changes of vital signs (heart rate, body temperature, and respiratory rate) have a certain value in the early prediction of anastomotic leakage after rectal cancer surgery. Observation of postoperative vital signs at 7 days postsurgery is helpful for the early diagnosis of anastomotic leakage.